Is the way an oil spill response is reported in the media important for the final perception of the clean-up?. Issue 1 (15th March 2016) - Chilvers, B.L.; Finlayson, G.; Ashwell, D.; Low, S.I.; Morgan, K.J.; Pearson, H.E.
Abstract: This research investigates the media coverage during the C / V Rena grounding in New Zealand (NZ), in 2011, to analyze if information reported in printed media is important for the final perception of the overall oil spill response. We took all articles available from NZ's largest circulated newspaper and the regional newspaper closest to the incident and analyzed the themes within each article; the article's tone (positive, neutral or negative); the time of the report relative to incident events and any differences between the regional and national papers. This analysis indicates that oil spills are reported and perceived as inherently negative incidents. However, along with coordinating an effective spill response, fast, factual and frequent media releases and increased effect in media liaison in areas of response with high public intrinsic value such as oiled wildlife response can significantly influence tone of media coverage and likely overall public perception. Highlights: Media coverage of the C / V Rena grounding and oil spill response was investigated. Articles were analysed for themes, tone and regional and national differences. Analysis indicates oil spills are reported and perceived as inherently negative. However, fast, factual frequent media releases & coverage of high intrinsic value areas wildlife, can influence tone perception.